Reaction of Desmodium species and other tropical pasture legumes to the root-knot nematode Meloidogyne javanica - Lenné, Jillian M. (1981)
The detection of the root-knot nematode, Meloidogyne javanica, as a pathogen of Desmodium spp. in Colombia, is the first reported case in South Aemerica. In the field, promising pasture legumes D. gyroides, D. heterocarpon and D. ovalifolium were severely damaged, while adjacent stands of Centrosema, Leucaena, Stylosanthes and Zornia spp. were not affected. In greenhouse trials with 38 tropical pasture legumes, only 13 accessions, including 10 of Desmodium spp. were susceptible. Accessions of D. distortum, D. heterophyllum, Leucaena leucocephala, Pueraria phaseoloides, Stylosanthes spp. including 6 Australian commercial cultivars, and Zornia latifolia were resistant. Although M. javanica has a narrow pasture legume host range and a very limited distribution throughout pasture evaluation sites, its pathogenicity to promising Desmodium spp. merits future surveys to determine its occurrence in the major pasture regions of tropical South America.